Head-to-head study of [18F]FAPI-04 PET/CT and [18F]FDG PET/CT for non-invasive assessment of liver cancer and its immunohistochemical markers - Zhiying Liang; Hao Peng; Wei Li; Zhidong Liu (BMC Cancer)
Abstract Objective To compare the performance of [18F]FDG and [18F]FAPI-04 in PET/CT evaluation for liver cancer lesions, with a further exploration of the associations between PET semiquantitative data and immunohistochemical markers to liver cancer. Methods Patients with suspected malignant liver lesions (MLL) underwent [18F]FDG and [18F]FAPI-04 PET/CT scanning. Liver lesions were visually classified as positive or negative based on their uptake level exceeding that of adjacent normal liver tissue. SUVmax and tumor-to-background ratio (TBR) were recorded for semi-quantitative analysis. Sensitivity, specificity and accuracy of each tracer were determined using pathological findings as the gold standard. Furthermore, immunohistochemical analysis provided the molecular characteristics of all MLLs. Comprehensive analysis explored correlations between these molecular markers and PET semiquantitative parameters (SUVmax andTBR) to identify potential associations. Results The study enrolled 44 patients, with 39 confirmed cases of MLL, comprising 28 hepatocellular carcinomas (HCC) and 11 intrahepatic cholangiocarcinomas (ICC). For MLL detection, [18F]FAPI-04 and [18F]FDG exhibited sensitivities of 84.6% (33/39) and 76.9% (30/39), specificitiesy of 60% (3/5) and 100%(5/5), and accuracy of 81.8% (36/44) and 79.5%(35/44). Across all liver lesions, [18F]FAPI-04 significantly surpassed [18F]FDG in SUVmax(10.54 ± 6.72 VS. 7.68 ± 6.79) and TBR(4.35 ± 3.78 Vs. 3.17 ± 3.05). Notably, [18F]FAPI-04 displayed markebly elevated SUVmax in benign liver lesions (BLLs) (P = 0.032), HCCs (P = 0.005), and ICCs (P = 0.011). Lesions with hepatocyte negativity (P = 0.023), CD34 negativity(P = 0.044), and high Ki67 expression (> 30%) (P = 0.001) had higher SUVmax on [18F]FAPI-04. Additionally, ARG-1-negative lesions demonstrated higher TBR on [18F]FAPI-04 than ARG-1-positive lesions(P = 0.018). No significant SUVmax/TBR differences were observed with [18F]FDG based on these markers. A linear relationship was identified between Ki67 scores and SUVmax of [18F]FAPI-04 (R = 0.603, P < 0.001). Conclusion [18F]FAPI-04 exhibits superior performance over [18F]FDG in PET/CT evaluation of liver cancer, characterized by increased sensitivity and SUVmax/TBR. Significant correlations with molecular markers, including Ki67, suggest [18F]FAPI-04’s potential for characterizing liver cancer subtypes and assessing tumor proliferation. However, further research is required to validate these findings and their clinical significance. Trial registration NCT05485792, Registered 01 August 2022.